Expressional STAT3/STAT5 ratio is an independent prognostic marker in colon carcinoma - Klupp, Fee; Diers, Johannes; Kahlert, Christoph; Neumann, Lena; Halama, Niels; Franz, Clemens; Schmidt, Thomas; Lasitschka, Felix; Warth, Arne; Weitz, Jürgen; Koch, Moritz; Schneider, Martin; et al. (Annals of surgical oncology, 2015)
Signal transducer and activator of transcription proteins (STATs) are crucial regulators of cell growth and differentiation; however, their specific prognostic impact in human colon cancer has only been studied to limited extent. We aimed to assess the prognostic significance of specific STAT expression patterns in colon carcinoma.